Trypanosome MKT1 and the RNA-binding protein ZC3H11: interactions and potential roles in post-transcriptional regulatory networks - Singh, Aditi; Minia, Igor; Droll, Dorothea; Fadda, Abeer; Clayton, Christine; Erben, Esteban D. (Nucleic acids research, 2014)
The trypanosome zinc finger protein ZC3H11 binds to AU-rich elements in mRNAs. It is essential for survival of the mammalian-infective bloodstream form, where it stabilizes several mRNAs including some encoding chaperones, and is also required for stabilization of chaperone mRNAs during the heat-shock response in the vector-infective procyclic form. When ZC3H11 was artificially ‘tethered’ to a reporter mRNA in bloodstream forms it increased reporter expression. We here show that ZC3H11 interacts with trypanosome MKT1 and PBP1, and that domains required for both interactions are necessary for function in the bloodstream-form tethering assay.